IMPLEMENTASI PENDEKATAN COLLABORATIVE FOR THE ADVANCEMENT OF SOCIAL AND EMOTIONAL LEARNING (CASEL) DALAM PEMBELAJARAN YANG BERPUSAT PADA PESERTA DIDIK - Arif Fahmi Ritonga; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
"Collaborative for Academic, Social and Emotional Learning" (CASEL) groups the components of emotional social learning into five components: (a) Self-awareness, the ability to understand emotions, thoughts, and values that influence behavior in different situations, (b) Self - management, the capacity to effectively regulate emotion, thinking, and behaviour in different circumstances, (c) Responsible decision making. (Pengambilan keputusan yang bertanggung jawab). Making the right and constructive choices in a particular situation (d) Social awareness (kesadaran sosial). The ability to understand different perspectives includes empathy for the circumstances of individuals with different backgrounds. (e) Relationship skills. Participant-centric learning emphasizes the concept of active learning where learning leads to the optimization of the intellectual and emotional bondage of students in full, so that the teacher is only a facilitator in the learning activities of students directed to learn and process the learning acquisition of knowledge, skills, attitudes, and values. Keywords: Casel, Learners, Teacher